MANAJEMEN SUPERVISI AKADEMIK PENGAWAS UNTUK MENINGKATKAN KOMPETENSI PAEDAGOGIK GURU MADRASAH (Studi Kasus di Madrasah Tsanawiyah Swasta KBB) - Budi Komara; Hanafiah Hanafiah; Faiz Karim Fatkhullah (Penerbit Widina, Widina Media Utama, 2026)
Background: Academic supervision is a strategic instrument for teacher mentoring and professional development. However, its implementation in private madrasas often faces structural, cultural, and technical constraints, which impact the stagnation of teachers' pedagogical competence improvement. Objectives: This study aims to describe and analyze the management of madrasah supervisors' academic supervision based on the POAC functions (Planning, Organizing, Actuating, Controlling) and its effectiveness in improving the pedagogical competence of teachers in Private Madrasah Tsanawiyah in West Bandung Regency. Methods: The research used a qualitative approach with a multisite case study method in three private MTs. Data were collected through observation, in-depth interviews with 3 supervisors, 9 teachers, and 3 madrasah principals, and documentation studies. Data analysis followed an interactive thematic analysis model. Results: The findings reveal that the four POAC management functions in academic supervision are not yet optimal. Planning is top-down and lacks needs assessment; organizing is constrained by supervisor-madrasah ratios and time; implementation is dominated by brief observations with normative feedback; and evaluation and follow-up are almost non-existent. Consequently, the impact of supervision on improving teacher pedagogical competence is minimal and only visible in administrative aspects. Conclusions: Academic supervision in the research locus experiences decoupling, where formal activities are separated from the substantive goal of teacher development. Reformulation of policies, restructuring of supervisor workloads, strengthening clinical supervision capacity, and transformation of supervision culture towards collaborative-participatory approaches are needed.ABSTRAKLatar Belakang: Supervisi akademik merupakan instrumen strategis dalam pembinaan dan pengembangan profesional guru. Namun, implementasinya di madrasah swasta sering kali menghadapi kendala struktural, kultural, dan teknis, yang berimplikasi pada stagnasi peningkatan kompetensi pedagogik guru. Tujuan: Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis manajemen supervisi akademik pengawas madrasah berdasarkan fungsi POAC (Planning, Organizing, Actuating, Controlling) serta efektivitasnya dalam meningkatkan kompetensi pedagogik guru Madrasah Tsanawiyah Swasta di Kabupaten Bandung Barat. Metode: Penelitian menggunakan pendekatan kualitatif dengan metode studi kasus multisitus di tiga MTs swasta. Data dikumpulkan melalui observasi, wawancara mendalam dengan 3 pengawas, 9 guru, dan 3 kepala madrasah, serta studi dokumentasi. Analisis data mengikuti model analisis tematik interaktif. Hasil: Temuan penelitian mengungkapkan bahwa keempat fungsi manajemen POAC dalam supervisi akademik belum berjalan optimal. Perencanaan bersifat top-down dan minim analisis kebutuhan; pengorganisasian terkendala rasio pengawas-madrasah dan waktu; pelaksanaan didominasi observasi singkat dengan umpan balik yang normatif; serta evaluasi dan tindak lanjut nyaris tidak ada. Akibatnya, dampak supervisi terhadap peningkatan kompetensi pedagogik guru sangat minimal dan hanya terlihat pada aspek administratif. Kesimpulan: Supervisi akademik di lokus penelitian mengalami decoupling, di mana aktivitas formal terpisah dari tujuan substantif pengembangan guru. Diperlukan reformulasi kebijakan, penataan ulang beban kerja pengawas, penguatan kapasitas supervisi klinis, dan transformasi budaya supervisi menuju kolaboratif-partisipatif.